Subjectivity : ethnographic investigations - Biehl, João; Good, Byron; Kleinman, Arthur (Ethnographic studies in subjectivity, 2007)
This innovative volume is an extended intellectual conversation about the ways personal lives are being undone and remade today. Examining the ethnography of the modern subject, this preeminent group of scholars probes the continuity and diversity of modes of personhood across a range of Western and non-Western societies. Contributors consider what happens to individual subjectivity when stable or imagined environments such as nations and communities are transformed or displaced by free trade economics, terrorism, and war; how new information and medical technologies reshape the relation one h.